JENIS DAN KELIMPAHAN MIKROPLASTIK PADA AIR DI PESISIR PANTAI MONPERA KOTA BALIKPAPAN KALIMANTAN TIMUR - yani, ade; Rafii, Akhmad; Ghitarina (Jurnal Tropical Aquatic Sciences, 2024)
Plastic waste found on the coastal, mainly caused by human activities that creatc pollution in coastal waters. Plastic waste can be found on the shoreline, floating on the surface of the waters and floating in the waters. The research was conducted in the coastal area of Monpera beach, Balikpapan City to determine the presence of micro-sized plastic waste (< 5 mm), identify the types of microplastics and analyze the abundance between types of microplastics. Samples were taken using a purposive sampling method with an area of 100 m long and aligned with the coastline. Microplastic samples in water were conducted base on 5 liter water container at a depth of approximately 0-20 cm. The highest number of identified microplastics were fragments with a total 5.986 particles/300L, 1.300 films particles/300L, 447 fibers particles/300L. In microplastics there was a significant difference between species abudance (sig p 0,004 < sig α 0,05).